A systematic review of the impact of postpartum depression on child development (Research, Society and Development, 2024)
Postpartum depression is defined by the World Health Organization as a type of depression that can appear in women, as the name suggests, after giving birth. It is characterized by intense feelings of sadness, anxiety and exhaustion, which can impair a mother's ability to care for herself and her baby. This study aimed to carry out a systematic review on the degree of harmfulness of this pathology throughout the child's life. This method was used following the recommendations of the PRISMA statement, which consists of a checklist of 27 elements and a flow diagram, to help authors improve review communication. The search in the databases was carried out between March and July 2024. 11 articles were included in the study. The results indicate that the impacts of postpartum depression on child development are very complex and can cause losses immediately in the first year of life, such as nutritional deficits, psychomotor delays or delays in language development, in addition to being removed from the mother. Later, there may be changes in behavior, risk of triggering childhood depression, and impaired concentration and learning, both in the family and school environment. The present study concludes by drawing the attention of competent authorities to the importance of research into postpartum depression and its impact on child development. Furthermore, it is recommended that future investigations be carried out focused on identifying risk and protective factors for victims of this disease, both mother and baby.